Phytochemical Screening and Toxicity Test of Various Extracts from Microalgae Dunaliella salina - Yosi Yananda Sijabat; Wilis Ari Setyati; Retno Hartati (Faculty of Fisheries and Marine Universitas Airlangga, 2023)
Highlight Research Extract N-hexane of salina contains alkaloids, steroids, triterpenoids, and phenols Extract Ethyl Acetate of salina contains alkaloids, steroids, triterpenoids, phenols, flavonoid, and saponins Extract Methanol of salina contains alkaloids, steroids, triterpenoids, phenols, flavonoid, and saponins 24- hours LC50 value of the n-hexane extract salina was 276 ppm, the ethyl acetate extract was 673 ppm and the methanol extract was 811 ppm. All of the three extracts were included in toxic category Abstract Microalgae are single celled microorganisms as the primary producers in the water food cycle. Microalgae bioactive compounds was estimated to be 10 times more diverse than compounds produced by land plants. Microalgae use nutrients more efficiently to grow, metabolize, and produce chemical compounds. Dunaliella salina is a type of chlorophyte microalgae with a lot of potential to be used in various fields. This study aimed to determine the phytochemical compound content and the value of lethal toxicity (24-hour LC50) in microalgae D. salina extract with different solvents. The multistage maceration method uses n-hexane, ethyl acetate, and methanol to extract samples. Phytochemical screening uses reagents according to the content of secondary metabolites. The Brine Shrimp Lethality Test method is used to test toxicity. The extracts were tested by using 10 Artemia salina against five concentrations, namely 0, 1, 10, 100, and 1000 ppm. Toxicity data were processed through probit analysis to get the 24-hour LC50 value. The results showed that alkaloids, steroids, triterpenoids, and phenols were found in the methanol, ethyl acetate, and n-hexane extracts. Saponin were found in the methanolic extracts. Flavonoid were found in the methanol and ethyl acetate extracts. The 24-hour LC50 value of the n-hexane extract was 276 ppm, the methanol extract was 811 ppm, and ethyl acetate extract was 673 ppm. The three extracts were included in toxic category. Extracts of microalgae D. salina have plenty secondary metabolite, that can be used in various fields and holds the potential as an anticancer.